Rancang Bangun Prototype Penjemuran Gabah Otomatis Berbasis Internet of Things - Junaidi; Elmi Devia; Wasjud Satrio (CV. Multi Kreasi Media, 2022)
Rice produced by rice farmers in Cikeusal Kidul village has not yet reached BULOG standards. This is caused by the drying process of grain that is too long or even too short. The process of drying grain in Cikeusal Kidul village is still done manually depending on the natural weather which is certainly quite draining. The purpose of this research is to help farmers in Cikeusal Kidul village to produce good quality grain according to BULOG standards, by building an Internet of Things (IoT) based automatic grain drying system. The system built has several functions, including: opening and closing the roof of the clothesline automatically, controlling temperature and humidity, animal repellent, and measuring grain humidity. The system built can be controlled and monitored remotely using the virtuino application and the Messenger Telegram Bot.